Tribological properties of modified phenolic resin ceramic friction materials - CHEN Hai-long; YANG Xue-feng; WANG Shou-ren; LU Chong-yang; WU Yuan-bo (Cailiao gongcheng, 2019)
Three kinds of phenolic resin ceramic brake pads were prepared with phenolic resin, boron modified phenolic resin, melamine modified phenolic resin as binder, and ceramic fiber as reinforcing fiber. The impact toughness and hardness of the material were tested. The friction and wear properties were investigated by friction and wear tester. The worn surface morphology and its composition were analyzed by scanning electron microscope (SEM) and X-ray energy spectrometer, and the wear mechanism was also discussed. The experimental results show that boron modified phenolic resin binder can improve the hardness of friction materials, melamine modified phenolic resin can improve the impact toughness of materials, reducing material hardness; in the friction process, melamine modified phenolic resin carbonized at high temperature, forming a dense layer of friction on the surface of friction material. The existence of friction layer makes the friction coefficient of the friction material become relatively stable, and reduces the wear rate of the friction material.